Diversidade beta espacial e temporal de peixes em um rio tropical fragmentado. - Buzo, Matheus Gimenez (2023)
The overexploitation of natural resources by human beings in recent centuries has had serious consequences for biodiversity. In freshwater aquatic environments, organisms suffer from various degradation processes, which involve pollution, environmental fragmentation, introduction of invasive species, among others. The construction of dams and reservoirs for energy production is among one of the biggest reasons for the degradation of these environments, as this fragments the water body, preventing connectivity between sites, in addition to transforming the lotic environment into a lentic one, completely changing the dynamics of the local. As an aggravating factor, there are reservoir cascades, which consist of a sequence of reservoirs built on the same river, enhancing the negative effects of a single reservoir. In highly fragmented environments, physical-chemical changes occur, which harm the local biological communities. Thus, in this work, analyzes of the spatial and temporal beta diversity of fish were carried out in a very fragmented river in northeastern Brazil, the São Francisco River. For spatial beta diversity, we calculated the Local Contribution to Beta Diversity (LCBD), taxonomic and functional, at 28 points along the six reservoirs and in a lotic stretch downstream of the reservoirs, up to the mouth. We performed a beta regression model to verify the relationship between LCBD values and environmental variables collected in the same period. As a result, we found that the points of the initial reservoirs and the points closest to the mouth of the river were the ones that most contributed to beta diversity, both taxonomic and functional, and turbidity was the variable that was most positively associated with LCBD values. For the temporal beta diversity analysis, we used five reservoirs, and compared the beta diversity between pairs of months over years. A correlation was also made between the results of temporal beta diversity and the variation of environmental variables. There was no relationship between environmental variables and temporal beta diversity. However, it was possible to observe that the reservoirs that operate as a trickle of water had the most unstable and unpredictable temporal beta diversity values, while the reservoir that operates as an accumulation followed the pattern of seasonal variation of the dry-flood dynamics. We recommend the proper management of the reservoirs of a waterfall, monitoring the variations in the parameters and regulating the flow and water level according to the expected natural variations, mainly the initial ones that function as sources of species and functional traits, and also the preservation of the rivers tax. We conclude that deeper studies covering other periods must be carried out, to complement the existing data and provide greater assertiveness in decision-making and conduction of reservoir operations.